identification of new genomic regions conferring leaf rust résistance in durum wheat - CGIAR Research Program on Wheat (2020)
New genomic regions identified conferring leaf rust resistance on chromosomes 1B, 2B,5B and 6B, QTL mapping, flanking markers identified and KASP markers need to be developed and followed up